Design of a workstation for teleoperated forwarders : Exploring the future work within forestry - Persson, Tobias (Luleå tekniska universitet, Institutionen för ekonomi, teknik och samhälle, 2020)
This thesis work has been the result of a five-year Industrial Design Engineering education at Luleå University of Technology. The project has investigated the possibilities of teleoperating forest machines using a human-centered design approach. The work has been conducted for Skogforsk, which is the Swedish institute for forestry. The project’s objective was to present ideas on how future teleoperation can improve the work as a forwarder operator. The aim was to identify the forwarder operators’ specific needs and explore how the development of a teleoperated workstation can address those needs. The project has been carried out using three phases; Inspiration, Ideation, and Impleentation. During the first phase, the project investigated how the work is carried out today and what needs a forwarder operator has. The operators’ needs can be summarised in three different areas; transporting the machine, loading and unloading, and planning. Two kinds of operators can be seen today, the ones who are motivated primarily by working in the forest, and the ones who are motivated by the production and self-competitiveness. During the Inspiration phase, the project also tested what problems exist today with operating a forwarder using teleoperation with the system implemented in the Truedsson Forestry Lab in Uppsala. It was identified that screens are an essential complement to using head-mounted displays such as VR-goggles while not offering the same amount of precision and presence in work as the goggles. It was also identified that the operators did not feel that the machine being an extension of them due to lost feedback of motion and sound. Perceived and actual control of the machine differed, and the operators did not identify the machines’ behavior during transportation. Apart from these issues, the current view did not offer a complete overview of the area around the machine. Neither did it offer visuals on the sides of the machine, and the logs sortings. Along with the identified issues, opportunities for ...